Speculations on the possibilities of indigenous origins of capoeira and on the contributions of this cultural matrix on the development of the game-fight - LUSSAC, Ricardo Martins Porto (Brazilian journal of physical education and sport, 2015)
The origin of Capoeira has been investigated and discussed until today. Several researchers in different fields and even capoeiristas themselves disagree about its genesis. These dichotomies persist in clashes in the field of Capoeira. In this article the assumptions about the indigenous Capoeira, and the possible contributions of Brazilian Indians in the development of game-fight.were analyzed, interpreted and discussed. Literature and documents were used as methodological procedure and a qualitative analysis of the sources that were interpreted and discussed throughout the narrative of this work was done. It was found that there was the possibility of interaction between blacks and Indians in cultural exchanges that would allow influences in the development of Capoeira. However, it was concluded that it is not possible to say that there are Brazilian indigenous contributions to the origins of Capoeira. Thus, we can say that the only and important Brazilian indigenous contribution is the nominal origin of the practice, for having the word capoeira tupy source. It is recommended that future studies are accomplished using the notes made in this article and analyzing primary sources that were not possible to be included in this paper.